Marchandisation et patrimonialisation du végétal : les critères esthétiques de la création variétale de roses coupées - Mathilde Fautras; Blandine Veith (Belgeo)
The commodification and patrimonialization of nature have often been studied separately or considered as contradictory. Following research that highlights the combination of these social logics in tension, this article questions their intertwining by focusing on a seemingly innocuous ornamental plant : the rose intended for bouquets. The paper focuses on the process of creation, which is less studied than that of production or preservation, in order to analyse the characteristics of the new varieties, commercial objects with symbolic values and codified uses. Based on empirical data, the article shows the evolution of cut roses bred in Europe and produced in Kenya, by tracing the partial diffusion of the aesthetic of pseudo-ancient varieties. It shows how the intertwining of market and heritage logics, materialised in the aesthetics of a plant, shed light on the dynamics of a globalised production sector.